2022
DOI: 10.1017/s0033291722003634
|View full text |Cite
|
Sign up to set email alerts
|

Dropout from psychological treatment for borderline personality disorder: a multilevel survival meta-analysis

Abstract: Background Dropout from psychotherapy for borderline personality disorder (BPD) is a notorious problem. We investigated whether treatment, treatment format, treatment setting, substance use exclusion criteria, proportion males, mean age, country, and other variables influenced dropout. Methods From Pubmed, Embase, Cochrane, Psycinfo and other sources, 111 studies (159 treatment arms, N = 9100) of psychotherapy for non-forensic adult patients with BPD were included. Dropout per quarter du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…On the other hand, more large-scale RCTs are currently underway. For example, Arntz et al ( 2022 ) published an RCT ( n = 495), and reported similar effect sizes for ST compared to TAU on BPD-severity as the present NMA. Fourth, we noticed that not all RCTs including participants with BPD actually measured overall BPD severity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…On the other hand, more large-scale RCTs are currently underway. For example, Arntz et al ( 2022 ) published an RCT ( n = 495), and reported similar effect sizes for ST compared to TAU on BPD-severity as the present NMA. Fourth, we noticed that not all RCTs including participants with BPD actually measured overall BPD severity.…”
Section: Discussionsupporting
confidence: 62%
“…To gain more insight into the actual treatment acceptability, future studies should measure treatment drop-out more homogeneously, for example by using similar definitions. A recent meta-analysis by Arntz et al ( 2022 ) investigated dropout rates from psychological treatments for BPD. Based on their findings, they also recommend future studies to better distinguish between different types of dropout (treatment dropout v. study dropout), by defining them more clearly according to guidelines [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the attendance level positively correlates with the sustained outcome data and specific attention to the cultivation of safeness in the therapeutic process in CFGP which has been cited as a missing component in other therapies (Barnicot et al, 2022). This attrition rate was lower than that of published literature reviews of treatments for people with a diagnosis of personality disorder which indicated 37% non-completion rate (Arntz et al, 2023;Hummelen et al, 2007;McMurran & Ward, 2010). This study and others have also recommended the use of preparation and engagement programmes to reduce attrition (Barnicot et al, 2022;Haigh &Pearce, 2017;McMurran, 2012;Webb & McMurran, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…"Limited reparenting" is regarded as the most important change mechanism 235 . Therapists try to compensate for the deficits in par enting that patients with BPD experienced during their childhood, while maintaining professional boundaries.…”
Section: Schema Therapy (St)mentioning
confidence: 99%
“…In many studies, risk of bias was high 17,205 , possibly inflating effect sizes 205 . Dropout rates are high 234 and differ considerably between studies 235 . Furthermore, treatment effects are found to be unstable at follow‐ups 17,205 .…”
Section: Managementmentioning
confidence: 99%